PARTISIPASI PEREMPUAN DALAM KEPEMIMPINAN SEBAGAI KEPALA DESA DI DESA PANCANEGARA KECAMATAN PABUARAN KABUPATEN SERANG BANTEN - Sa'adiyyah, Ade Millatus; Andiyani, Gita Indri (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2025)
ABSTRACT This research was conducted in Pancanegara Village, Pabuaran District, Serang Regency, with the aim of 1) To find out the low number of women in village government leadership. 2) To find out what are the challenges of women's participation in the local political process. 3) To find out the strategy of increasing women's participation in local politics.The research method used is descriptive analysis research with a qualitative approavh/information directly from information sources that are considered related to Women’s Participation in Leadership as Village Heads in Pancanegara Village, Pabuaran District, Serang Regency, The informants/resource persons were the Head of Pancanegara Village, Pancanegara Village Staff and several Pancanegara Village communities. The results of this study show the lack of participation of women in local politics or as village heads in Pancanegara Village. Lack of awareness in the community where the community considers women to be less professional in their work. The conclusion of this study is that the Village Head has made efforts to increase women's participation in local politics in Pancanegara Village. Village heads and village governments have carried out several activities to increase women's interest in participating in local politics. Women's Participation, Leadership, Village Head.